The twilight saga. New moon [compact disc] : original motion picture soundtrack. - Yorke, Thom; Lykke Li, 1986-; Marina, Anya; St. Vincent, 1982-; Legrand, Victoria; Desplat, Alexandre (Atlantic, 2009)
One of the most anticipated big-screen sequels ever is accompanied by an equally exciting, more indie-rock centric soundtrack. It features the single Meet Me on the Equinox by Death Cab for Cutie.